2019
DOI: 10.1177/1756287219838364
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of randomized controlled trials that assess the efficacy of low-intensity shockwave therapy for the treatment of erectile dysfunction

Abstract: Background: The aim of this study was to perform a meta-analysis of randomized controlled trials (RCTs) that evaluate the efficacy of low-intensity extracorporeal shock wave therapy (LiESWT) for the treatment of erectile dysfunction (ED). Materials and methods: A comprehensive search of PubMed, Medline , and Cochrane databases was performed from November 2005 to July 2018. RCTs evaluating efficacy of LiESWT in the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 41 publications
(150 reference statements)
2
32
0
Order By: Relevance
“…Erectile dysfunction is another condition of interest in cancer rehabilitation [911]. This indication can also be treated with ESWT, but has to be managed in an interdisciplinary setting [2].…”
Section: Commentarymentioning
confidence: 99%
“…Erectile dysfunction is another condition of interest in cancer rehabilitation [911]. This indication can also be treated with ESWT, but has to be managed in an interdisciplinary setting [2].…”
Section: Commentarymentioning
confidence: 99%
“…11 Men with severe ED with DM, advanced age, and/or hypertension often have less response to drugs and often require additional management strategies. 12 Platelets have an important role in promoting wound healing and coagulation and include several growth factors responsible for regenerative functions (eg, fibroblast growth factor, platelet-derived growth factor, vascular endothelial growth factor [VEGF]). 13 Therefore, owing to these growth factors, it has the potential to support the regenerative matrix and healing in damaged tissues.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Men with severe ED with DM, advanced age, and/or hypertension often have less response to drugs and often require additional management strategies. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analysis demonstrated that the mean difference of IIEF-EF score between the treatment and sham groups was 4.23 (p=0.012) at the 1-month follow-up. No significant adverse events were reported [ 94 ]. These studies suggest that LI-SWT appears to produce significant improvement of the IIEF and EHS and appears to be well-tolerated.…”
Section: Emerging Therapies For Erectile Dysfunctionmentioning
confidence: 99%